ANALISIS EVALUASI HIGHER ORDER THINGKING SKILLS (HOTS) PADA KELAS TINGGI DI SDN KUWONHARJO 2 KECAMATAN TAKERAN KABUPATEN MAGETAN - Septi Aprilia (LPPM STKIP PGRI Sidoarjo, 2020)
This study aims to analyze the formative evaluation developed by the teacher so it is known whether the evaluation form developed is based on High Order Thinking Skills (HOTS). The subjects of this study were High School Students of SDN Kuwonharjo 2, Academic Year 2018/2019 UPTD Takeran District, Magetan Regency. The research approach used is descriptive qualitative approach. The data of this study were obtained from formative question documents developed by SDN Kuwonharjo 2 teachers. Based on the overall results of the formative evaluation analysis, it showed that the evaluation forms that were made had not yet demonstrated Higher Order Thinking Skills (HOTS). All questions are still at the C1 and C2 levels so this is an ingredient to make improvements in terms of planning to make a minimum evaluation form at the C4 level.